When Courts and Politics Collide: Mongolia’s Constitutional Crisis - Ganzorig, Gombosuren (Columbia Journal of Asian Law, 2001)
Mongolia’s political system has received well-deserved attention as one of the most successful examples of democratization in the Asian region Since 1990, Mongolia has undergone peaceful constitutional change and has conducted several democratic elections. Human rights are well- respected, the media is free and political competition exists? This is all the more remarkable given that constitutional democracy has developed “without prerequisites,” that is, without a previous history of democracy or social pluralism that is sometimes thought necessary for democracy to flourish. During the early years of transition, Mongolia’s Constitutional Court played an important role in facilitating democratic change. The court occasionally overturned parliamentary legislation while serving as a vehicle to protect human rights and the constitutional scheme. However, in recent years Mongolia’s Constitutional Court has found itself at the center of a major controversy regarding the very structure of the political system. Through a series of decisions that has placed it at odds with the legislature, the Court has raised questions about its ability to play an appropriate role in a constitutional democracy. This article traces the origins of the current problems with the Mongolian constitutional scheme and describes the Court’s role in precipitating the political crisis. <footer></footer>